2020
DOI: 10.1088/1742-6596/1491/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Parameters (σ, ε) of Lennard-Jones for Fe, Ni, Pb for Potential and Cr based on Melting Point Values Using the Molecular Dynamics Method of the Lammps Program

Abstract: Lennard-Jones potential is the potential energy of the bond interaction between two atoms or free molecules based on the distance between them. Molecular dynamics simulations can be used to calculate various physical properties of materials based on specific interaction potentials. One of the physical properties of a material is its melting point. This research was conducted to find the potential parameter values of Lennard-Jones metal Fe, Pb, Ni and Cr based on the melting point value of the material using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Table 4 gives the Lennard–Jones 6–12 parameters and partial charges for PbO, which were taken from Refs. 62 , 63 . We first tested the PbO force field parameters by determining internal energies of departure as a function of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 gives the Lennard–Jones 6–12 parameters and partial charges for PbO, which were taken from Refs. 62 , 63 . We first tested the PbO force field parameters by determining internal energies of departure as a function of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The interatomic interactions within and between the ILs were described by the OPLS-AA force field based on LigParGen . Interactions within the iron substrate were modeled using the Lennard–Jones (LJ) potential with ϵ = 0.2007 eV and σ = 2.4193 Å . Interactions between the substrate and the ILs were modeled using the LJ potential combining the Fe parameters with the LJ parameters of OPLS-AA using geometric mixing rules …”
Section: Methodsmentioning
confidence: 99%
“…65 Interactions with the iron substrate were modeled using the Lennard-Jones (LJ) potential with ϵ ss = 0.2007 eV and σ ss = 2.4193 Å. 66 Interactions between substrate and ILs were modeled using the LJ potential, combining the Fe parameters with the LJ parameters of OPLS-AA using geometric mixing rules. 67 It has been found that contact angle generally increases linearly with droplet size until it converges to a constant values after a critical number of ions or droplet radius is reached.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…The [NiFe] cofactor had bond constraints placed across the CN and CO ligands as well as between the iron atom and two bound sulfur atoms. Lennard-Jones parameters were taken from the Charmm36m [89,90] forcefield where appropriate, with exception of the cyanuric carbon [95] with the iron parameters taken from physical data to have a non-zero epsilon value [96]. The QL molecular oxygen model developed by Javanainen et al [97] was chosen to better define the quadrupole within the molecule.…”
Section: Molecular Dynamics Parameterization and Simulationmentioning
confidence: 99%